EFEKTIFITAS SERBUK DAUN SPEARMINT (Mentha spicata) SEBAGAI REPELLENT TERHADAP KECOA RUMAH (Periplaneta americana) - Mandasari Br Ginting; evi naria; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
Effectivity of spearmint leaves powder as repellent to american cockroach. American cockroach (Periplaneta americana) is mechanical vector which can bring agent of diseases. In Cockroach had ever been found about 40 microorganism so that can contaminate human food and cause some intestinal diseases even the allergic for human.Usually, People control the American cockroach by using chemical substances which persistent in environment if we use it continuously. This research showed that there was differences average of the quantity of American cockroach which can pass spearmint leaves powder at observation after five minutes with p =0,048. There wasn’t differences average of the quantity of American cockroach at observation after ten minutes and fifteen minutes with p= 0,064 and p= 0,059. The calculation of average protection power of spearmint (Mentha spicata) leaves powder as a repellent to the american cockroach (Periplaneta americana) showed that there wasn’t average protection power over than 90%. The conclusion of this study showed that there there wasn’t average protection power over than 90%. So that spearmint (Mentha spicata) leaves powder wasn’t effective to used as repellent to the american cockroach (Periplaneta americana). Keywords: repellent, american cockroach (Periplaneta americana), spearmint (Mentha spicata)